Kinetic analysis of HER2-binding ABY-025 Affibody molecule using dynamic PET in patients with metastatic breast cancer; EJNMMI Research; Vol. 10, iss. 1 - Alhuseinalkhudhur A. Ali; Lubberink M. Mark; Lindman H. Henrik; Tolmachev V. M. Vladimir Maksimilianovich; Frejd F. Y. Fredrik; Feldwisch J. Joachim; Velikyan I. Irina; Sorensen J. Jens (2020, 2020)
Title screen